FABRICATION OF NOVEL ANTICANCER POLYOXOMETALATE [CoW11O39(CpTi)]7- -CHITOSAN NANO-COMPOSITE, ITS TOXICITY REDUCTION AND SUSTAINED RELEASE - Pandya, Vamangi M; Joshi, Sachin A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Polyoxometalates (POMs) are proved to be important for applications in medicine and in material science. Here, we represent nanocomposite formation of tungsten-containing potent anticancer polyanion, K 6 H [CoW 11 O 39 Â (CpTi)].13H 2 O (CoW CpTi) with biocompatible ChitosanYC-100 (CSYC100) with the goal to reduce its heavy metal toxicity. Methods: Synthesis of POM-CSYC100 nanocompositeâ€ was attained without the aid of any cross-linker through electrostatic interaction technique.Â Nanocomposites were characterized using Fourier transform infrared spectroscopy, dynamic light scattering, transmission electron microscopy, andÂ thermogravimetric analysis. The release profile recorded was slow and sustained at physiological pH. In vitro cytotoxicity assays which show an attribute to reduce the toxicity of these POM were performed on C2C12 (mouse myoblast cell line) and A-549 (lung cancer cell line), which proved theÂ reduced toxicity of nanocomposites as compared to the bare drugs. Results: Sustained release studies showed there was a slow and steady release of CoWÂ CpTi for 11 hrs, with the 98% of collective release at theÂ end. From in vitro cytotoxic assay, it was deduced that CoWÂ 11Â 11 CpTi -CSYC100 nanocomposite at the concentrations of 1.25 mM, and lower did notÂ exhibit toxic effect on C2C12 cells as 95% total C2C12 cell mass remained viable. While in the case of A549 cells highest 5 mM concentration of bareÂ CoWÂ 11Â CpTi is toxic to the cancer cells and after encapsulation cell viability increases from 10% to 55%. Conclusion: Thus, this study has designated the probability of using POM-chitosan nanocomposite for less toxic and effective biomedicinal applications. Keywords: Anticancer, Chitosan, Nanocomposite, In vitro cytotoxicity, Drug release.